First Record of Boa Constrictor (Serpentes, Boidae) in the Quaternary of South America - Albino, Adriana Maria (2008)
Vertebral remains assignable to the extant snake Boa constrictor, found in the Toropí Formation (Late Pleistocene, Lujanian age) at Arroyo Toropí, northeastern Argentina, are here described. These remains represent the first snake record from the Lujanian age and determine the minimum age for the species as 50–35 ka BP. Boa is presently absent in northeastern Argentina. Interruption of the continuity between the Mesopotamian and Brazilian faunas, including disappearance of Boa from Mesopotamia (northeastern Argentina), occurred subsequent to the Late Pleistocene and might be explained by changes in the Paraná and Uruguay Rivers. In addition, previous taxonomic referral of fossils to ?Boa is revised, with the conclusion that the specimen from the Early Eocene is tentatively referred to this genus, whereas that from the Pliocene is an indeterminate Boinae.